EFFECTS OF FADAMA III USER GROUP PARTICIPATION ON FOOD SECURITY OF RURAL HOUSEHOLDS IN BENUE STATE, NIGERIA. - ADEYEMI , E. B.; ADEYEMO , R.; KEHINDE , A. D.; FAMUYINI , C. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study determined the food security status and analysed the influence of Fadama III project on food security of the rural households in Benue State. Multistage sampling technique was used. Data were collected using structured questionnaires. Data obtained were analysed using foster, greer and thorbecke index (food expenditure approach) and double hurdle model. The mean age of the participants and non-participants were 42 years and 48 years respectively. Participants (71%) and non-participants (62%) were male and majority of participants (72%) and non-participants (70%) were married. The average household sizes were 7.1 and 6.5 for participants and non-participants respectively. The severity of food insecurity among the participants of Fadama III project was 0.04 while among the non-participants was 0.06. The result of the double hurdle showed at the first hurdle that farming experience (p<0.05), non-farm income (p<0.01), participation (p<0.1) and household size (p<0.01) were significant factors affecting the food security status in the study area. The result of the second hurdle revealed that age (p<0.05), household size (p<0.01), farming experience (p<0.01), participation (p<0.1) and access to credit (p<0.01) were the significant factors influencing the severity of food security in the study area. In conclusion, participation in Fadama III project had a positive and significant influence on food security. Therefore, farmers should be encouraged to participate more in the project in order to improve the level of food security in Nigeria.